Prevalence of Edentulism and Crowding in Subjects of a Known Population - bhagat, Ashish; Das, Dipika; Bali, Esha; Salkar, Manjiri; Chelkar, Shubham; Singh, Heram (Journal of Neonatal Surgery, 2025)
Background: This study was conducted to assess the Prevalence of Edentulism and Crowding in Subjects of a Known Population. Material and methods: This study comprised of 100 subjects. The individuals had been informed about the procedure and were asked for consent. All the participants underwent oral clinical examination and the prevalence of crowding and edentulism was noted and the findings were tabulated. Statistical analysis had been conducted using SPSS software. Results: In this study, there were 64 males and 36 females. It was observed that edentulism was seen in 23 patients and crowding was observed in 11 patients. Conclusion: From the findings of this study, it can be concluded that prevalence of edentulism and crowding was 23% and 11%, respectively.